IMPLEMENTATION OF GRAPHIC ORGANIZERS AND INTERACTIVE WAY, «TRIAL» IN THE TEACHING PROCESS - Nishanbayeva A.T (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The article presents the importance of modern educational technologies in the educational process to develop creative and analytical thinking of students, as well as to secure the threads passed to laboratory and practical training. The article deals with the implementation of graphic organizers, such as Venn diagrams, and interactive way «TRIAL» in the learning process.